2021
DOI: 10.1007/s11469-021-00506-1
|View full text |Cite
|
Sign up to set email alerts
|

Social Exclusion, Self-Forgiveness, Mindfulness, and Internet Addiction in College Students: a Moderated Mediation Approach

Abstract: Internet addiction is a growingly prevalent behavioral addiction that causes numerous psychosocial problems. Investigating the causes and consequences of Internet addiction is fundamental to comprehend and prevent it. Therefore, the current study provided protective and promotive factors for undesired effects of social exclusion on Internet addiction. The study examined a moderated mediation model to test whether mindfulness moderated the mediating role of self-forgiveness in the association between social exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 80 publications
3
17
0
Order By: Relevance
“…Privacy concerns are also important; as such, posts about drinking alone may be particularly suited for targeting potential problem drinkers due to the likelihood these posts have been publicly shared. During COVID-19, average social media addiction scores similar to those in this study have been reported among college students (Arslan et al, 2021 ), although the amount of time spent on SNS tends to be even greater than that reported in the present study (Zhao & Zhou, 2020 ). That social media use frequency has been associated with adherence to COVID-19 guidelines yet social media addiction is inversely related with adherence (Cooper et al, 2020a , 2020b ) suggests that redirecting college students to seemingly healthier uses of social media (while not crossing into the addictive use range) seems optimal to enhance both individual and public health.…”
Section: Discussionsupporting
confidence: 85%
“…Privacy concerns are also important; as such, posts about drinking alone may be particularly suited for targeting potential problem drinkers due to the likelihood these posts have been publicly shared. During COVID-19, average social media addiction scores similar to those in this study have been reported among college students (Arslan et al, 2021 ), although the amount of time spent on SNS tends to be even greater than that reported in the present study (Zhao & Zhou, 2020 ). That social media use frequency has been associated with adherence to COVID-19 guidelines yet social media addiction is inversely related with adherence (Cooper et al, 2020a , 2020b ) suggests that redirecting college students to seemingly healthier uses of social media (while not crossing into the addictive use range) seems optimal to enhance both individual and public health.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have confirmed that social exclusion is one antecedent of Facebook addiction as well as internet addiction (Poon, 2018;Lim, 2019;Arslan and Coşkun, 2021). Some scholars have also found that social exclusion can positively and significantly predict substance use disorder and other addictive behaviors (Rabinovitz, 2014;Bacon and Engerman, 2018;Wesselmann and Parris, 2021).…”
Section: The Relationship Between Social Exclusion and Smartphone Add...mentioning
confidence: 88%
“…In China, college students have more disposable money than junior high school students and senior high school students, but the correct concept of consumption has not been fully formed, so the possibility of impulsive buying is also higher. What is more, a large number of previous studies have shown that social exclusion will have a serious and far-reaching negative impact on college students, such as internet addiction [ 3 ] and depression [ 4 ]. Therefore, it is of great significance to explore the relationship between social exclusion and college students’ impulsive buying.…”
Section: Introductionmentioning
confidence: 99%